Amalan Animisme Dan Dinamisme Dalam Masyarakat Acheh : Kajian Kes Di Acheh Utara Dan Kota Lhokseumawe [GN471. R547 2008 f rb]. - Hasan, Ridwan (2008)
Nanggroe Acheh Darussalam (NAD) as documented in history is the first Islamic State in South East Asia in the 16th and 17th century. The Islamic teachings exercised by the Muslim society of Acheh originated from Gujerat, India, However, these teachings are a mixture of cultures and traditions taken from the Shiite and Hindu cultures.